Fracture resistance of immature teeth filled with mineral trioxide aggregate, bioaggregate, and biodentine - Bayram, Emre (Eur J Dent, 2016)
OBJECTIVE: The purpose of this study was to evaluate fracture resistance of teeth with immature apices treated with coronal placement of mineral trioxide aggregate (MTA), bioaggregate (BA), and Biodentine. MATERIALS AND METHODS: Forty-one freshly extracted, single-rooted human premolar teeth were used for the study. At first, the root length was standardized to 9 mm. The crown-down technique was used for the preparation of the root canals using the rotary ProTaper system (Dentsply Maillefer, Ballaigues, Switzerland) of F3 (30). Peeso reamer no. 6 was stepped out from the apex to simulate an incompletely formed root. The prepared roots were randomly assigned to one control (n = 5) and three experimental (n = 12) groups, as described below. Group 1: White MTA (Angelus, Londrina, Brazil) was prepared as per the manufacturer's instructions and compacted into the root canal using MAP system (Dentsply Maillefer, Ballaigues, Switzerland) and condensed by pluggers (Angelus, Londrina, Brazil). Group 2: The canals were filled with DiaRoot-BA (DiaDent Group International, Canada). Group 3: Biodentine (Septodont, Saint Maur des Fosses, France) solution was mixed with the capsule powder and condensed using pluggers. Instron was used to determine the maximum horizontal load to fracture the tooth, placing the tip 3 mm incisal to the cementoenamel junction. Mean values of the fracture strength were compared by ANOVA followed by a post hoc test. P < 0.05 was considered statistically significant. RESULTS: No significant difference was observed among the MTA, BA, and biodentine experimental groups. CONCLUSION: All the three materials tested, may be used as effective strengthening agents for immature teeth.